Uji Beberapa Konsentrasi Ekstrak Daun Bintaro (Cerbera manghas L.) Berpelarut Organik untuk Mengendalikan Ulat Bawang Merah (Spodoptera exigua Hubner) - Ryan Afriandi Siregar; Rusli Rustam (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2022)
ABSTRACT Shallot caterpillar (Spodoptera exigua Hubner.) is a major problem in onion cultivation. Spodoptera exigua can cause yield loss of 45-57% and can cause crop failure. Controls are generally carried out using synthetic insecticides, but the continuous use of synthetic insecticides can have a negative impact on humans and the environment. One alternative control that can be used is a vegetable insecticide with organic solvents from Bintaro leaf extract (Cerbera manghas L.). The study was aimed to obtain the concentration of bintaro leaf extract using an effective organic solvent to kill Spodoptera exigua larvae on shallots. This research was conducted at the Laboratory of Organic Chemistry and Natural Materials, Faculty of Engineering, Laboratory of Plant Pests and Laboratory of Experimental Gardens, Faculty of Agriculture, Riau University from July to September 2021. This research was conducted experimentally using a Completely Randomized Design (CRD) with six treatments and four treatments. replicates to obtain 24 experimental units. The treatments were bintaro leaf extract concentrations of 0%, 0.2%, 0.4%, 0.6%, 0.8%, and 1%. The results showed that a concentration of 1% was an effective concentration in killing Spodoptera exigua larvae of 87.50% with the fastest early death time at 12 hours after application, Lethal time 50 at 53 hours after application, and the highest daily mortality occurred on the third day, namely 35% after 5 days after application.Keywords : Bintaro leaf, Shallot, Spodoptera exigua Hubner